Characterization of Crude Protease Bacillus sp 31 - Esti Utarti; Lina Nurita; Sattya Arimurti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Bacillus sp 31 was bacteria which produce protease. Characterization of protease from Bacillus sp 31 i.e. pH, temperature, influence of metal ion, enzyme kinetic and enzyme termostability is important to get optimal enzyme activity. Protease activity showed values 146.40 U/ml on pH 9 and optimal temperature 60°C by value. Protease activity increased by addition of 159.50 U/ml Fe2+, but its activity decreased by addition of Mg2+, Cu2+, Ca2+, Al2+, Zn2+ dan Mn2+. Maximal velocity (Vmax) of enzyme-catalysed reactions was 21.32 U/ml with Km 1.5x10-3 mg/ml (Michaels-Menten Kinetic). Protease was very stable at 60°C for 4 hours of incubation and 7 hours of half-time.